The Novel and Media: Three Essays. - Frow, John; Hardie, Melissa; Rich, Kelly (Journal of Language, Literature & Culture, 2019)
The article presents three essays on topics that were discussed at the Novel and Media conference held at Harvard University's Mahindra Humanities center in May 2018. Topics discussed include role of novels as a narrative genre and various forms of digital media; resurgence of formalist analysis in literary criticism by thinking about the intersection of the novel form, novel theory, and media studies; and relation between the print medium in which the novel originated and the other media.